Decentering methodological nationalism to survey precarious legal status trajectories. Issue 2 (4th March 2022) - Landolt, Patricia; Goldring, Luin; Pritchard, Paul
ABSTRACT: We examine how the politics of knowledge production limit research on the relationship between immigration status and social inequality. We centre the practices of methodological nationalism in Canada, a traditional country of permanent immigration in which temporary migration has become a core feature of the immigration system. In this case, state classification and counting of populations, and the careful curation of data on nominally permanent and temporary migrants limits research on immigration status. We also document the research design process and survey instrument we developed to work towards methodological autonomy from the state categorization of people on the move. The research design included community consultations, democratization of the research process, and a commitment to experiential knowledge. The resulting survey offers a parsimonious instrument to study complex and indeterminate precarious legal status trajectories and their relationship to social inequality.